2015
DOI: 10.1186/s12893-015-0013-5
|View full text |Cite
|
Sign up to set email alerts
|

Survival after laparoscopic and open surgery for colon cancer: a comparative, single-institution study

Abstract: BackgroundSome recent studies have suggested that laparoscopic surgery for colorectal cancer may provide a potential survival advantage when compared with open surgery. This study aimed to compare cancer-related survivals of patients who underwent laparoscopic or open resection of colon cancer in the same, high volume tertiary center.MethodsPatients who had undergone elective open or laparoscopic surgery for colon cancer between January 2002 and December 2010 were analyzed. A clinical database was prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
3
19
1
Order By: Relevance
“…Previously randomized controlled studies demonstrated that LR benefits favorable operative outcomes with less pain, quick recovery of the gastrointestinal tract, a shorter hospital stay and better cosmetics when compared with OR [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously randomized controlled studies demonstrated that LR benefits favorable operative outcomes with less pain, quick recovery of the gastrointestinal tract, a shorter hospital stay and better cosmetics when compared with OR [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy provides a better visualization of intra-abdominal conditions [27], including a wider, clearer and brighter image to allow surgeons to perform a more radical and precise resection of the mesocolon and mesorectum, while facilitating an accurate and complete lymphadenectomy [28,29]. Complete lymphadenectomy for colorectal cancer is essential for the patient's oncological prognosis due to reduced risk of residual nodal disease, and accurate nodal staging (achieving a better stratification of tumor staging) [19]. We noted no statistical difference in lymph node retrieval number between our two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The favourable post-operative complication rate following laparoscopic resection for CRC has been well documented over the past decade. [ 2 5 6 7 8 9 10 11 13 14 15 16 27 28 29 ] However, only a few studies have compared the morbidity outcome following ML and CL approaches for CRC. The present study demonstrated a superior morbidity profile after ML compared with that after CL.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the number of patients included in this study was relatively small. The patients who underwent or were converted to open surgery were excluded because the numbers of LNs retrieved are different, which would result in bias . In addition, only about 10% ( n = 35 during the study period) of the patients undergo open surgery for CRC at our centre, which would result in a subgroup too small for reliable statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with rectal cancer located below the peritoneal reflection were excluded from this study because of the complicated pattern of metastases to the lateral pelvic nodes. Patients with fewer than 12 retrieved LNs, open surgery (because of significant differences in the numbers of harvested lymph nodes between open surgery and laparoscopy), synchronous tumours, neoadjuvant treatment and familial adenomatous polyposis (FAP) were also excluded from the present study. This study was reviewed and approved by the ethics committee of Mianyang Central Hospital.…”
Section: Methodsmentioning
confidence: 99%